2000
DOI: 10.1021/ja993064m
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolic Link between Arsenite and Selenite:  The Seleno-bis(S-glutathionyl) Arsinium Ion

Abstract: Among the most startling observations in mammalian toxicology is that a lethal dose of selenium can be overcome by an otherwise lethal dose of arsenic. We report the molecular basis of this antagonism. Using X-ray absorption spectroscopy we have identified a new arsenic−selenium compound in the bile of rabbits injected with aqueous selenite and arsenite solutions. This compound contains equimolar arsenic and selenium and exhibits X-ray absorption spectra which are essentially identical with those of a syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
131
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(141 citation statements)
references
References 22 publications
8
131
2
Order By: Relevance
“…This hypothesis is supported by experimental studies indicating that As and Se each mutually facilitate biliary excretion of the other (Zeng et al 2005). A Se-As-glutathione complex, seleno-bis(S-glutathionyl) arsinium ion, [(GS) 2 AsSe] − , has been detected in biliary excretion of rabbits, suggesting that one potential mechanism whereby Se intake may reduce the body burden of As is by increasing its loss through biliary excretion (Gailer et al 2000), although this complex has not yet been definitively identified in humans. In this cross-sectional analysis, it is not possible to determine the temporal nature of the relationship between plasma Se and uAs/bAs or whether this is a causal relationship.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This hypothesis is supported by experimental studies indicating that As and Se each mutually facilitate biliary excretion of the other (Zeng et al 2005). A Se-As-glutathione complex, seleno-bis(S-glutathionyl) arsinium ion, [(GS) 2 AsSe] − , has been detected in biliary excretion of rabbits, suggesting that one potential mechanism whereby Se intake may reduce the body burden of As is by increasing its loss through biliary excretion (Gailer et al 2000), although this complex has not yet been definitively identified in humans. In this cross-sectional analysis, it is not possible to determine the temporal nature of the relationship between plasma Se and uAs/bAs or whether this is a causal relationship.…”
Section: Discussionmentioning
confidence: 75%
“…Several studies have indicated that As and Se each mutually facilitate excretion of the other in bile (Levander 1977). Recent work in rabbits indicates that this may occur via the formation of a Se-As-glutathione conjugate (Gailer et al 2000), although this has not yet been demon strated in humans. Other proposed mechanisms include direct interaction and precipitation of As and Se in renal cells and effects on cellular signaling, zinc finger proteins, and methylation pathways (Berry and Galle 1994;Zeng et al 2005).…”
Section: Researchmentioning
confidence: 99%
“…16 Although this compound is formed chemically, is it formed biologically? Indeed the bile from rabbits injected with selenite and arsenite is found by EXAFS studies to contain substantial amounts of 7.…”
Section: Ooo-trimethylselenophosphate 2 With Trimethylsilyl Iodide mentioning
confidence: 99%
“…11 Our animal studies conducted so far, however, have involved the administration of arsenite, selenite and selenate in the low milligram per kilogram body weight range because the physico-chemical techniques that were employed to identify the metalloid species in bile (namely XAS and SEC-ICP-AES) required these metalloid dose levels.…”
Section: Asse]mentioning
confidence: 99%
“…12 The combined application of X-ray absorption spectroscopy (XAS) and size-exclusion chromatography (SEC) with simultaneous multi-element-specific detection by inductively coupled argon plasma atomic emission spectroscopy (ICP-AES) eventually revealed that a previously unknown metabolite, the seleno-bis(S-glutathionyl) arsinium ion, [(GS) 2 AsSe] − , is excreted from the liver to the bile after the intravenous injection of New Zealand white rabbits with selenite followed by arsenite. 11,14 Subsequent studies revealed that [(GS) 2 …”
Section: Introductionmentioning
confidence: 99%